2013
DOI: 10.1111/ffe.12026
|View full text |Cite
|
Sign up to set email alerts
|

Internal–external circumferential crack behaviour in the cement layer of total hip replacement

Abstract: This study aimed to investigate crack behaviour at the internal and external surfaces of the cement layer in total hip replacement. A three‐dimensional model of the femur with the cemented prosthesis was developed and analysed. Cracks were placed on the internal, external and both internal and external surfaces of the cement layer. Stress intensity factors were measured during gait. Results revealed that the stress intensity factors modes I and III were the most dominant in the crack propagation in the cement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…(b), which is approximated from the saw‐bones catalogue by using photogrammetric software ImageJ to measure the cortical bone thickness at various points from cross‐sectional photographs. This was carried out to improve model accuracy over models, which assume uniform cortical‐bone thickness such as those presented by Oshkour et al and Cilingir et al . Because of the model's complex geometry, it was meshed in a commercial package (UGS NX 7.5) using tetrahedral elements set to a spacing of 2 mm.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…(b), which is approximated from the saw‐bones catalogue by using photogrammetric software ImageJ to measure the cortical bone thickness at various points from cross‐sectional photographs. This was carried out to improve model accuracy over models, which assume uniform cortical‐bone thickness such as those presented by Oshkour et al and Cilingir et al . Because of the model's complex geometry, it was meshed in a commercial package (UGS NX 7.5) using tetrahedral elements set to a spacing of 2 mm.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…However, coating could be flaked off from metals substrate because of weak bond between ceramic and metallic phases [ 21 ]. In addition, our several theoretical studies have shown that stress intensity factors at the external surface of the cement layer of the cement coated metallic implants are higher which may be the primary cause of easy flaking off of the coatings from the metallic surfaces [ 22 , 23 ]. Composites of many ceramics, including HA [ 13 , 24 ], CS [ 14 , 25 ], and alumina (Al 2 O 3 ) [ 5 , 26 ], have been used in different biomedical applications successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Different implant designs can be analyzed more accurately by conducting FEA in a computer rather than performing time‐consuming, destructive, and costly mechanical and in vivo tests . FEA is commonly conducted to study artificial hip joint biomechanics and femoral prosthetic designs . Many FEA studies have also focused on the optimization of the geometry and material of femoral prostheses to develop THR with a long lifespan .…”
mentioning
confidence: 99%